Building Coalitions: Mobilizing the Community - Barbara A. Brahm; Margaret E. Griffiths; Elizabeth B. Bolton; Lisa Guion (EDIS, 2002)
This document is FY502, Part 10 of the 16 part series adapted for use in Florida by Elizabeth B. Bolton and Lisa Guion. Reprinted with permission March, 1997. Revised April, 2002.